European network for the conservation and sustainable use of plant genetic resources in nature and on farm - Dulloo, Mohammad Ehsan; Maxted, Nigel; Kell, Shelagh; Negri, Valeria; Iriondo, Jose; Hintum, Theo van; Drucker, Adam G.; Bartha, Béla; Fehér, Judit; Maierhofer, Helene; Magos Brehm, Joana; Palmé, Anna; et al. (2022)
This policy brief presents the key achievements of the Farmer’s Pride project (horizon 2020 project)., that underpin and have enabled the establishment of a European in situ (in-nature) PGR network. Some of the key objectives of Farmer’s Pride are to: (a) improve on-farm and in situ conservation of landraces (LR) and crop wild relatives (CWR), (b) back-up or safety duplicate the seeds of these precious resources through ex situ (off-site) storage, and multiplication in national gene banks and community seed banks, (c) ensure wide accessibility and use of these conserved resources, (d)Harmonize and better integrate formal conservation and informal dynamic conservation management efforts at the global, regional, or national level.